2022
DOI: 10.30621/jbachs.1018224
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Time to Ambulation on Patient Outcomes, Anxiety and Depression

Abstract: Purpose: The aim of the study was to investigation of the effects of time to ambulation on patient outcomes, anxiety and depression. Method: This is a descriptive cross-sectional study. The study was conducted on 157 patients in the general surgery clinic of a training and research hospital in western Turkey. The data were collected using a Descriptive Form, Patient Outcomes Follow-up Form, Brief Pain Inventory, Hospital Anxiety and Depression Scale (HADS) and analysed by number, percentage, Mann–Whitney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…In our study, patients experienced high levels of nausea-vomiting-retching in the postoperative period according to the RINVR (the total RINVR score -24.1 ± 0.91) and the sub-dimensions of symptom experience, symptom occurrence, and symptom distress. There was a significant relationship between patients' preopera-tive anxiety and postoperative nausea-vomiting, in other words, patients who had high preoperative anxiety experienced more postoperative nausea and vomiting [58]. These results were consistent with the results obtained by Majumdar et al (2019) and Laufenberg-Feldmann et al (2019) who suggested that preoperative anxiety increased postoperative nausea [20,33].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, patients experienced high levels of nausea-vomiting-retching in the postoperative period according to the RINVR (the total RINVR score -24.1 ± 0.91) and the sub-dimensions of symptom experience, symptom occurrence, and symptom distress. There was a significant relationship between patients' preopera-tive anxiety and postoperative nausea-vomiting, in other words, patients who had high preoperative anxiety experienced more postoperative nausea and vomiting [58]. These results were consistent with the results obtained by Majumdar et al (2019) and Laufenberg-Feldmann et al (2019) who suggested that preoperative anxiety increased postoperative nausea [20,33].…”
Section: Discussionsupporting
confidence: 90%